Lichen Pseudocyphellaria Mapping in Cibodas Botanical Garden Conservation Park - Supratman, Lilis; Sudirman, Lisdar; Suryadharma Putra, Okky (Journal Of Biology Education Research (JBER), 2025)
Lichens are symbiotic organisms between fungi and algae. In Indonesia, lichen inventory research is very limited. Several Lichen families have entered critical levels such as Lobariaceae. The purpose of this study was to: record and collect the Lobariaceae family as a rare lichen, analyze population data of the Lobariaceae family, growth percentage and development of Lobariaceae family transplants. This research method used exploration with calculations based on the surface area of ​​tree trunks, the number and coverage of thallus, and thallus coverage per square meter for each tree. The results of this study found 340 Pseudocyphellaria thallus consisting of Pseudocyphellaria sp. P. aurata, P. crocata and P. argyracea. During one year of Pseudocyphellaria transplantation, there was no growth in terms of increasing thallus cover. The development that occurred was that the transplant was able to attach well to the substrate. It is estimated that Pseudocyphellaria thallus takes longer to adapt well to the substrate to grow and develop. The conclusion of this study is that the transplanted lichen showed satisfactory growth, which indicates that this method can be used for the conservation of threatened lichen species.